(untitled) (Jurnal Ipteks Terapan, 2024)
This research examined the differences in mathematical economics’ learning outcomes taught with STEM Education and explicit instructions. This research used a quasi-experimental method with a non-equivalent design. The population of this research was IBBI University students, totaling 40 students. The sample selection in this research used simple random sampling. The data collection technique in this research used high high-order thinking-based test. The data analysis technique in this research used an independent sample t-test. The results showed a significant difference between mathematics learning outcomes taught with STEM Education and Explicit Instruction. In conclusion, the two s are different in application, but both can improve mathematical economics learning outcomes.